Comparison of Titanium Dioxide Nanocrystal with Hydrothermal Method and P25 Degussa for Photocatalytic Arsenic - Diana Rakhmawaty E; Astri Aldelina; Atiek Rostika N (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: Arsenic is one of 10 chemicals which is harmful to human health, according to WHO. Arsenic that harmful to human health is generally in the form of inorganic compounds with oxidation number of 3 (As(III)). One of the best known method to remediate As(III) is an oxidation method. Titanium dioxide (TiO2) can be used as a photocatalyst to oxidize As(III). The photocatalytic activity of TiO2 is highly dependent on the size and composition of the crystal phase. Smaller size of TiO2 crystal can be obtained by using hydrothermal method. This study aimed to compare the synthesized TiO2 with P25 Degussa to As(III) reduction. Materials used are TiCl4 as a precursor and H2SO4 and t-butanol as solvents. The crystal structure of synthesized TiO2 is a mixture of anatase and rutile with a greater composition of anatase than rutile. The TiO2 crystal size is calculated using scherrer equation and showed that the crystal size is less than 60 nm. The ability of synthesized TiO2 using H2SO4 2.0 M in the reduction of As(III) concentration is 72% exceeded the capability of P25 Degussa is 35%. Keywords: As(III), hydrothermal, H2SO4, t-butanol, TiO2 photoactivity